Осіле тваринництво у носіїв салтівської культури на Дону - Колода, В.В.; Горбаненко, С.А. (Археологія і давня історія України, 2010)
У статті розглянуто матеріали з тваринництва, притаманного осілій частині носіїв салтівської археологічної культури, як степової, так і лісостепової зони. Висвітлено історію досліджень та існуючий нині археозоологічний матеріал, розглянуто знахідки знарядь тваринництва з поселень Сіверсько-Донецького регіону, споруди тваринництва, а також окреслено імовірні типові місця для випасання худоби. В статье рассмотрены материалы по оседлому животноводству, свойственному носителям салтовской археологической культуры. Основу для анализа составляют археозоологические материалы с 9 памятников. В результате исследования определены некоторые различия между памятниками, находящимися в разных природных условиях; рассчитано вероятное мясное производство. Также привлечены археологические материалы (орудия животноводства, археологические объекты), свидетельствующие о животноводстве. Общий вывод состоит в том, что в подавляющем большинстве животноводство было на одинаковом (высоком) уровне с земледелием, эти отрасли органично взаимодополняли друг друга. The article comprises materials concerning settled livestock breeding that is typical for the Saltov culture people. The basis for the analysis is archeozoological materials from nine sites. In the result of the research there have defined some differences between the sites, located in various natural conditions; probable meat production has been estimated. Also the archeological artifacts (livestock breeding implements, archeological objects) that are indicative of livestock breeding have been involved. The general conclusion describes the fact that in overwhelming majority livestock breeding had the same high level with agriculture; these sectors complemented each other in an organic way.